Urban planning aspects of stability theory of ecological town planning systems - Ustinova, Iryna (Transfer of innovative technologies, 2018)
The study of the problems of sustainable devel-opment of the ecological and urban planning system " population ↔ environment" of various levels of its functional and spatial integrity (lo-cal, regional, national, world-wide) reveals a number of fundamental provisions that estab-lish the conceptual foundations of a new direc-tion in urban planning science that potentially exists in certain individual works. The development of urban planning aspects of the stability theory is based on the funda-mental concept of the physico-mathematical stability theory that is more developed at the present time and the research findings, which established the cyclical nature of the multilevel processes of wave development of the "popula-tion ↔ environment" system. The urban plan-ning stability theory studies the nature of the vi-brational development of urbanization process-es accelerating in a multi-level ecological space. The paper reveals a number of similarities and fundamental differences in the states of stability and the dynamic pattern that are inher-ent in the development of living and inanimate natural systems. Regarding the differences in state of equilibrium: equilibrium is the goal of development for living systems within a certain cycle and the level of their spatial integrity. For inanimate systems equilibrium is the initial state. Concerning the differences in the stability of the location of the "center of mass": the "center of mass" should occupy the highest possible position (in the range of ecological equilibrium) for living systems; for the inanimate-to take the lowest possible position. When developing the urban development aspects of stability theory were used such concepts of physical and mathematical stability theory as: asymptotic stability; stability "in time" according to Lyapunov; stability "in space" ("stable − unstable node", "stable − non-stable focus ", "stable center"). Marked con-cepts are important for the analysis of multi-level processes of accelerating development of the ecological and urban planning system; fore-casting the direction of its further changes; de-termination of focuses and parameters of appli-cation of urban planning regulatory influences; adapted sustainable development management.